Understanding the world language edTPA : research-based policy and practice - Hildebrandt, Susan A.; Swanson, Peter, 1964- (Contemporary language education (Greenwich, Conn.), 2017)
In Understanding the World Language edTPA: Research-Based Policy and Practice, two researchers in the forefront of world language edTPA discuss the new beginning teacher portfolio, including its required elements, federal and state policies concerning teacher evaluation, and research from their own programs. Higher education faculty members and language teacher preparation program coordinators who would like to better understand edTPA requirements and gain suggestions for necessary programmatic changes will find this book of interest.The book is composed of eight chapters. The authors begin by describing edTPA and how it became a national trend to assess beginning teacher ability. In Chapter 2, the authors present ideas about curricular changes that may need to occur in traditional world language teacher education programs, as well as suggestions to assist teacher candidates as they begin to develop their portfolios. Afterward, the authors discuss the context for learning (Chapter 3) and they begin with assessment, moving to planning, and then to instruction (Chapters 4, 5, 6). In each chapter, the authors discuss the work sample that teacher candidates must create, an analysis of a high-scoring portfolio, and steps to stimulate teacher candidates' professional thinking. In Chapter 7, the authors present activities for the methods classroom. In the final chapter, the authors provide a critical analysis of edTPA, in general, and the world language edTPA, in particular.Understanding the World Language edTPA: Research-Based Policy and Practice provides readers with a much-needed guide to inducting teacher candidates into the new portfolio requirements, while helping higher education faculty make appropriate curricular changes to accommodate edTPA.